Disclosing the essentiality of ribose-5-phosphate isomerase B in Trypanosomatids - Faria, J (2016)
Ribose-5-phosphate isomerase (RPI) belongs to the non-oxidative branch of the pentose phosphate pathway, catalysing the inter-conversion of D-ribose-5-phosphate and D-ribulose-5-phosphate. Trypanosomatids encode a type B RPI, whereas humans have a structurally unrelated type A, making RPIB worthy of exploration as a potential drug target. Null mutant generation in Leishmania infantum was only possible when an episomal copy of RPIB gene was provided, and the latter was retained both in vitro and in vivo in the absence of drug pressure. This suggests the gene is essential for parasite survival. Importantly, the inability to remove the second allele of RPIB gene in sKO mutants complemented with an episomal copy of RPIB carrying a mutation that abolishes isomerase activity suggests the essentiality is due to its metabolic function. In vitro, sKO promastigotes exhibited no defect in growth, metacyclogenesis or macrophage infection, however, an impairment in intracellular amastigotes' replication was observed. Additionally, mice infected with sKO mutants rescued by RPIB complementation had a reduced parasite burden in the liver. Likewise, Trypanosoma brucei is resistant to complete RPIB gene removal and mice infected with sKO mutants showed prolonged survival upon infection. Taken together our results genetically validate RPIB as a potential drug target in trypanosomatids.